Differences in Soaking Time of Sea Urchin Gonad Extract (Diadema setosum) on Nile Tilapia (Oreochromis niloticus) Masculinization with a Dose of 4 mg/L : Perbedaan Lama Perendaman Ekstrak Gonad Bulu Babi (Diadema Setosum) Terhadap Maskulinisasi Ikan Nila (Oreochromis Niloticus) Dengan Dosis 4 Mg/L - Sari, Mutiara Pradita; Susanto, Gregorius Nugroho; Widiastuti, Endang Linirin; Tugiyono, Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
Nile tilapia (Oreochromis niloticus) is a fish that is in demand because of its high economic value and thick meat. Tilapia is easy to breed, uncontrolled spawning can occur so that growth is inhibited. The growth of male tilapia is faster than females at the same age. To increase the growth rate, sex reversal is carried out towards males through immersion in steroid hormones. Bioactive substances contained in sea urchins are steroid compounds. The purpose of this study is to determine the effect of the length of immersion in sea urchin gonad extract (Diadema setosum) on the formation of male phenotypes of tilapia larvae and tilapia survival. The method used is a completely randomized design with 4 treatments and each treatment with 3 replicates at a dose of 4 mg/L with soaking times of 0, 12, 18, and 24 hours. Data are analyzed using SPSS 16 software with analysis of variance (One-way ANOVA). The results show that different lengths of immersion in sea urchin steroid extract at a dose of 4 mg/L affect the formation of male individuals. A soaking time of 18 hours is quite effective in directing the sex of fish to males by 66%. Immersion time also affects the survival of tilapia larvae.